Female knowledge about pelvic physiotherapy in primary care (Research, Society and Development, 2023)
Pelvic physiotherapy acts in the prevention of dysfunctions, rehabilitation of the pelvic floor and improves quality of life. However, due to the lack of disclosure, it does not reach visibility to the public that needs this service. The present study aimed to analyze what is the level of knowledge of women in the Federal District (DF) about the performance of pelvic physiotherapy in primary care?. The survey was conducted via Google Forms, with the participation of 171 women living in the Federal District with the age group of 18 to 80 years. The questionnaire was made available Online through links disclosed by social media and the collection was only started after the favorable opinion of the Research Ethics Committee. It was identified that 90.64% of women never sought pelvic physiotherapy and 7.6% said they had already sought it. Of those who have already sought, 15.38% went for prevention and 84.61% for treatment. The main complaints presented by women were vaginal itching with 35.7%, loss of libido with 33.9%, vaginal burning with 25.7% and urine leakage with 22.8%. In this way it was seen that pelvic physiotherapy still has a low visibility by the female public, where the treatment is the medium that some are still looking for within the area. Evidencing that this specialty needs more marketing strategies to disseminate and disseminate about this area, especially aimed at primary care. In this way, the female public will have more access to information, mainly aimed at prevention.